30.3: Comparison of On‐Screen Display‐based and ICC Profile‐based Calibration for OLED Displays. Issue 1 (1st July 2013) - Wu, Chih‐Lei; Badano, Aldo; Cheng, Wei‐Chung
Abstract: The tone reproduction curves of an OLED display were measured and modeled as a function of three on‐screen display (OSD) settings. The optimal OSD settings, derived from the model, outperformed two ICC profile‐based color calibration kits by reducing the calibration errors from 2.89% to 0.25% and the quantization errors from 9.28% to 0%.